Application of inline imaging for monitoring crystallization process in a continuous oscillatory baffled crystallizer. Issue 7 (12th March 2018) - Kacker, Rohit; Maaß, Sebastian; Emmerich, Jörn; Kramer, Herman
Abstract : In this study, an in situ imaging system has been analysed to characterize the crystal size, the shape and the number of particles during a continuous crystallization process in a Continuous Oscillatory Baffled Crystallizer (COBC). Two image analysis approaches were examined for particle characterization in the suspension containing both small nuclei and larger grown crystals (nonspherical and irregular in shape). The pattern matching approach, in which the particles are approximated to be spherical, did result in an overestimation of the size. Alternatively, a segmentation‐based algorithm resulted in reliable crystal size and shape characteristics. The laser diffraction analysis in comparison to the image analysis overestimated the particle sizes due to the agglomeration of particles upon filtration and drying. The trend in the particle counts during the start of crystallization process, including nucleation, determined by the image analysis probe was comparable with the one measured by FBRM, highlighting the potential of in situ imaging for process monitoring. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2450–2461, 2018